2020
DOI: 10.1080/20009666.2020.1800970
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital outcomes of angiography versus intravascular ultrasound-guided percutaneous coronary intervention in ST-elevation myocardial infarction patients

Abstract: (2020) In-hospital outcomes of angiography versus intravascular ultrasound-guided percutaneous coronary intervention in ST-elevation myocardial infarction patients,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
5
0
4
Order By: Relevance
“…1) [12,13,[21][22][23][24][25][26][27]. One eligible record was excluded because the study population was also part of a larger included study by Ya'qoub et al [26,28]…”
Section: Search Results and Study Selection Processmentioning
confidence: 99%
“…1) [12,13,[21][22][23][24][25][26][27]. One eligible record was excluded because the study population was also part of a larger included study by Ya'qoub et al [26,28]…”
Section: Search Results and Study Selection Processmentioning
confidence: 99%
“…1) [12,13,[20][21][22][23][24][25][26]. One eligible record was excluded because the study population was also part of a larger included study by Ya'qoub et al [25,27]…”
Section: Search Results and Study Selection Processmentioning
confidence: 99%
“…Moreover, in the IVUS-guided PCI group, the patients with optimal stent implantation revealed a signi cantly lower incidence of TVF compared to those with suboptimal stent implantation (1.6% vs. 4.4%; hazard ratio 0.35) [19]. Although no randomized controlled trial (RCT) have investigated the intracoronary imaging guidance in the setting of STEMI, the national database in the United States and a recent registry study in the United Kingdom reported that the number of intracoronary imaging use in patients presenting with ACS has steadily been increasing [20,21].…”
Section: Discussionmentioning
confidence: 99%